Extended reading: college students’ attitudes In selecting reading materials - Novika Amalia (UPT Bahasa Universitas Tanjungpura, 2020)
Appraising the trend that students are welcomed to independently make their own choices in learning, this study investigated college students’ preferences and considerations on self-chosen materials for extended reading (ER). A survey was conducted on 32 college students majoring in ELT who has taken reading courses. The survey consisted of ten questions, all related to their preferences and considerations in choosing the materials to read for ER activities. The results extracted led to the conclusions that authentic materials are more favorable over graded readers, and the difficulty level of the text considered as the foremost priority. Interested researchers are apprised to conduct an experiment that allows better and deeper analysis to gain insights on providing materials for ER in the EFL contexts for the students to select by themselves.